Financial Control Techniques Services Company with Fuzzy Mamdani - Marfalino, Hari; Putra, Muhammad Reza; Yulia, Guslendra c, Yosi (International Journal of Engineering and Technology, 2018)
Service Company is a business activity that provides products in the form of services to customers. Micro business services are in great demand among SMK graduates as it is very easy to live up to their abilities. This includes Micro Service Counter service, tailor, reflection, and others. However, the problem that arises is their lack of practical financial business knowledge. Many businesses they experience an emergency because they do not have proper business financial statements. With the current technological advances, most problems can be solved by technology. One such solution is an accounting information system application with mamdani blur technique. The process of calculating the system is done in 4 stages, namely: the formation of the blur set, the implications of the rules, the rules of composition and Defuzzyfication. Based on the results of trials, there’s an error in determining the price of services. Therefore, the high price of service can reduce the number of service requests and the low price service may incur losses to the company. With this system, one can determine the best service price and the best service for consumers.